Terminate with extreme prejudice an expose of the assassination game, its killers and their paymasters - Belfield, Richard (Pan Macmillan Australia Pty Limited, 2005)
Inside the assassination game - what really goes on before the smokescreens go up? 'Assassination can seldom be employed with a clear conscience. Persons who are morally squeamish should not attempt it...No assassination instructions should ever be written or recorded' - "CIA Assassination Manual", 1954. The cost of a bullet can be as little as 8 cents. Assassination has long been more common than anyone (particularly anyone in government) likes to admit - it is the great untold secret at the heart of the nation state. Now we are entering a new era of assassination where the '8-cent option' has never been more popular. Belfield's darkly fascinating expose of the business, its hired killers and their paymasters includes excerpts from CIA, Al Quaeda and Soviet assassination manuals. It sheds light on the most important hits of modern times. He gives an eye-opening account of how Kennedy made the Vietnam War inevitable by the elimination of President Diem; and clear evidence of assassinations where the official version simply is not true, including Bobby Kennedy, Yitzhak Rabin and WPC Yvonne Fletcher. And in a powerful conclusion he shows that the world underestimated the killing of President Sadat in 1981 - this apparently isolated incident was a trigger that heralded a new age of assassination 'solutions